An integral and MRAC-based approach to the adaptive stabilisation of a class of linear time-delay systems with unknown parameters - Ramírez Jerónimo, Luis Felipe; Saldivar, Belem; Aguilar-Ibanez, Carlos; Acosta, José Ángel (Zielona Góra: Uniwersytet Zielonogórski)
The design of a novel strategy based on the model reference adaptive control method for the stabilisation of a second-order linear time-delay system with unknown parameters is presented. The proposed approach is developed under the assumption that only one state of the system is available, and the sign of the control gain is known. First, the integral operator is applied to obtain a new representation of the original system, where the whole state is known. The use of the integral operator decomposes the control problem into two subproblems that are solved by using the model reference adaptive control method and the backstepping procedure. The effectiveness of the proposed approach is illustrated through an academic example and a practical application case regarding a chemical reactor recycle system.
Keywords: MRAC; time-delay systems; backstepping; integral operator